Development and Validation of Adaptive Learning Platform (ALP) to Improve Challenge-Based Mathematical Numeracy Literacy in Local Shoe Manufacturing Entrepreneurs - Muhammad Solihin; Rani Darmayanti; Ferra Rachma Auliya (CV. Edutechnium Indonesia, 2026)
This development research is based on the significant gap between the low Mathematical Numeracy Literacy of students (especially in reasoning and critical thinking) and the high demands of entrepreneurship in the context of Local Shoe Manufacturing, where the calculation of raw material costs, operational costs, and profit margins are crucial. The main objective of this research is to produce a blueprint and concept map for an Adaptive Learning Platform (ALP), which effectively integrates real industry challenges into applied mathematics materials, in line with the need for hyper-personalization and the trend of Intelligent Tutoring Systems in education. The Research Method used is the 4D Research and Development (R&D) Model which is limited only to the Define Stage. The research design involves four analytical steps: Needs Analysis, Concept Analysis, Student Characteristics Analysis, and Product Specifications. Data Collection Techniques include Curriculum Documentation Study, Industrial Field Observation (including online marketing practices), an in-depth interview with industry managers, a Systematic Literature Review, and an Initial Questionnaire for learning needs diagnosis. The main instruments include the Event Guidelines, Material Relevance Matrix, and Numeracy Test. Data analysis was conducted qualitatively-descriptively through triangulation data synthesis from various sources. The findings indicate an urgent need for an ALP with adaptive features and tracking mechanisms that present Percentage, Comparison, and Statistics materials in manufacturing product pricing scenarios, resulting in an ALP Prototype Blueprint (including adaptive flow charts and storyboards) ready for implementation in the next Design stage.